2D diamond-like functionalized nanosheets: physical properties and potential applications in alkali metal (Li, Na, K) ion batteries - Nascimento, Bruno Bueno Ipaves (2023)
In the context of the climate crisis due to human activities and the rapid increase of greenhouse gas emissions, renewable energy sources, such as solar and wind power systems, are promising solutions. Therefore, efficient technologies for storing electricity produced from these sources are essential. Among the various energy-storage devices, the lithium-ion battery (LIB) has been a leading option since entering the market in 1991. Nevertheless, it is crucial to develop rechargeable batteries beyond LIBs to meet the world\'s increasing demand for renewable energies. In this sense, two-dimensional (2D) materials have emerged as excellent candidates for applications in batteries. Therefore, this thesis presents an ab-initio investigation on the physical properties of 2D diamond-like functionalized nanosheets, performed in the framework of density functional theory. Herein, we explored the physical properties of diamond-like graphene nanosheets functionalized with nitrogen and boron atoms. Moreover, we investigated the diamond-like silicene nanosheets surface-doped with boron, nitrogen, aluminum, and phosphorus atoms. We predicted nanosheets with interesting physical properties that could possibly be applied in alkali metal ion batteries (AMIBs), van der Waals heterostructures, and ultraviolet light or thermoelectric devices. In particular, we studied and demonstrated the aluminum-functionalized silicene nanosheet is a promising candidate for AMIBs anodes, mainly for sodium and potassium ion batteries. This material remains stable up to about 600K and presents properties, such as surface diffusion barriers and specific capacity, similar to commercial anode graphite.